High sacrospinous fixation for managing recurrent pelvic organ prolapse, an innovative approach: a case report - Mahajan, Shreya; Valecha, Shalini Mahana; Rajput, Disha Andhiwal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
A case of 45-year-old female patient with recurrent pelvic organ prolapse (POP) following a previous vaginal hysterectomy and pelvic floor repair. Despite initial relief for 4 years, she again developed complaints of something coming out of vagina, leading to significant discomfort and functional impairment. Physical examination revealed complete vaginal vault eventration with cystocele and rectocele, along with a deficient perineum Preoperative evaluations confirmed the necessity and feasibility of surgical intervention. A specifically tailored approach was used to treat multiple pelvic floor defects using high sacrospinous fixation combined with Anterior colporrhaphy, posterior colpoperineorrhaphy and enterocoele repair. Postoperative outcomes demonstrated substantial improvement in symptoms and functional recovery, and overall restoration of pelvic floor supports. High sacrospinous ligament fixation (SSLF) is a safe, effective, and simple procedure for prevention and treatment of vaginal vault prolapse.